2021
DOI: 10.1101/2021.11.05.465894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct profiles of LRRK2 activation and Rab GTPase phosphorylation in clinical samples from different PD cohorts

Abstract: Despite several advances in the field, pharmacodynamic outcome measures reflective of LRRK2 kinase activity in clinical biofluids remain urgently needed. A variety of targets and approaches have been utilized including assessments of LRRK2 itself (levels, phosphorylation), or its substrates (e.g. Rab10 or other Rab GTPases). We have previously shown that intrinsic kinase activity of LRRK2 isolated from PBMCs of G2019S carriers is elevated, irrespective of disease status. In the present study we find that phosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One of the potential biomarkers currently studied is phospho-Ras-related protein Rab-10 (Rab10). However, although phospho-Rab10 is readily dephosphorylated in patient cells upon LRRK2 inhibition 54,55 , there are conflicting results regarding its ability to differentiate between PD and healthy individuals for example [55][56][57][58] . Moreover, biomarkers are still lacking that would discriminate between PD and atypical parkinsonian disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential biomarkers currently studied is phospho-Ras-related protein Rab-10 (Rab10). However, although phospho-Rab10 is readily dephosphorylated in patient cells upon LRRK2 inhibition 54,55 , there are conflicting results regarding its ability to differentiate between PD and healthy individuals for example [55][56][57][58] . Moreover, biomarkers are still lacking that would discriminate between PD and atypical parkinsonian disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase-activating mutations in the LRRK2 gene are strongly linked with familial PD (64) and contribute to enhanced risk of idiopathic PD (iPD) (63). It is also well established that LRRK2 kinase activation occurs in iPD independent of an activating mutation (16,65,66). The present study reveals that 10-NO2-OA dosedependently limits increases in rotenone-induced LRRK2 kinase activity in dopamine neurons and may represent a central mechanism of action 10-NO2-OA in countering aspects of PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated phosphorylated Rab10 has been observed in postmortem human brain tissue [7], peripheral immune cells [32], and blood from patients with iPD i . Additionally, preliminary results indicated that elevated phosphorylated Rab10 is present in peripheral blood mononuclear cells (PBMCs) in two cohorts of subjects with iPD [33]. These results suggest there is increased LRRK2 kinase activity or decreased phosphatase activity in iPD.…”
Section: Lrrk2: Substrates and Kinase Regulationmentioning
confidence: 98%